2022
DOI: 10.1002/jimd.12462
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel MPC1 gene variants causing mitochondrial pyruvate carrier deficiency

Abstract: Pyruvate, the end product of glycolysis, is a key metabolic molecule enabling mitochondrial adenosine triphosphate synthesis and takes part in multiple biosynthetic pathways within mitochondria. The mitochondrial pyruvate carrier (MPC) plays a vital role in transporting pyruvate from the cytosol into the organelle. In humans, MPC is a hetero-oligomeric complex formed by the MPC1 and MPC2 paralogs that are both necessary to stabilize each other and form a functional MPC. MPC deficiency (OMIM#614741) due to path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Once imported into mitochondria by the MPC, its metabolism is tuned by mainly two enzymes: pyruvate dehydrogenase (PDH), which converts pyruvate to acetyl-coA, and pyruvate carboxylase (PC), which catalyses the conversion of pyruvate to oxaloacetate in fasting conditions. Numerous cases of pathogenic variants disrupting the activity of PDH or PC, and recently MPC1, have been described, 14 , 17 , 18 all leading to severe diseases characterized by various phenotypes including lactic acidosis, hypotonia, developmental delay, seizures and even premature death. Here, we describe the first pathogenic MPC2 variants associated with an equally devastating multisystemic dysfunction in children.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Once imported into mitochondria by the MPC, its metabolism is tuned by mainly two enzymes: pyruvate dehydrogenase (PDH), which converts pyruvate to acetyl-coA, and pyruvate carboxylase (PC), which catalyses the conversion of pyruvate to oxaloacetate in fasting conditions. Numerous cases of pathogenic variants disrupting the activity of PDH or PC, and recently MPC1, have been described, 14 , 17 , 18 all leading to severe diseases characterized by various phenotypes including lactic acidosis, hypotonia, developmental delay, seizures and even premature death. Here, we describe the first pathogenic MPC2 variants associated with an equally devastating multisystemic dysfunction in children.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, MPC dysfunction contributes to cell proliferation in colorectal or prostate cancer 8,9 as well as pathological cardiac hypertrophy 10,11 , diabetic nephropathy 12 and it has also been shown that MPC is required for myocardial stress adaptation 13 . In humans, loss-of-function MPC1 variants prevented MPC assembly and mitochondrial pyruvate uptake 5,15 . To date, there are only 10 patients reported in the literature 15 , with clinical presentations including hypotonia, encephalopathy and frequent early death 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations